2019
DOI: 10.1093/rfs/hhz084
|View full text |Cite
|
Sign up to set email alerts
|

The Strategic Effects of Trademark Protection

Abstract: We study the effects of trademark protection on firms’ profits and strategy using the 1996 Federal Trademark Dilution Act, which granted additional legal protection to selected trademarks. We find that the FTDA raised treated firms’ operating profits and was followed by a spike in trademark lawsuits and lower entry and exit in affected product markets. Treated firms reduced R&D spending, produced fewer patents and new products, and recalled a higher number of unsafe products. Our results suggest that stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 47 publications
2
39
0
Order By: Relevance
“…The final validation asks if and how our the new estimates of intangible capital can explain previously established measures of patent values and trademark production. We find that the "Exits" stocks explain relatively more of the cross-sectional variation in patent valuations from Kogan, Papanikolaou, Seru, and Stoffman (2017) and the number of new trademarks filed by a firm in a given year (Heath and Mace, 2020).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…The final validation asks if and how our the new estimates of intangible capital can explain previously established measures of patent values and trademark production. We find that the "Exits" stocks explain relatively more of the cross-sectional variation in patent valuations from Kogan, Papanikolaou, Seru, and Stoffman (2017) and the number of new trademarks filed by a firm in a given year (Heath and Mace, 2020).…”
mentioning
confidence: 83%
“…40 Untabulated, we find that β2 is positive and significant with all capital stocks. 41 The data are available in the Internet Appendix of Heath and Mace (2020).…”
Section: Trademarksmentioning
confidence: 99%
“…To overcome the endogenous nature of a firm's trademarking activities, several studies have used the 1996 FTDA as an exogenous shock to examine how enhanced trademark protection affects firm outcomes. For example, Heath and Mace (2020) showed that stronger trademark protection increases firms' operating profits but has negative effects on firm innovation and product quality. Chiu et al (2019) found evidence that US public firms use trademarks as collateral to secure bank loans and that strengthened trademark protection decreases the cost of a firm's bank loans.…”
Section: Recent Literature On Trademarksmentioning
confidence: 99%
“…Several recent studies have adopted the FTDA as an exogenous shock to examine how increased trademark protection affects firm outcomes (Chiu et al, 2019;Heath & Mace, 2020). To make a causal link between trademarks and IPO underpricing in our paper, we follow these studies in introducing the FTDA in the context of our setting.…”
Section: 21mentioning
confidence: 99%
See 1 more Smart Citation